Learner English a teacher's guide to interference and other problems - Swan, Michael 1936-; Smith, Bernard (Cambridge Univ. Pr., 2001)
"Learner English is a well-established and successful reference book for teachers of British English. This new edition builds on the success of the original book. It has been rewritten and extended to provide information on the typical problems and error-patterns of a wide range of learners of English from particular language backgrounds. It compares the relevant features of the students' own language with English, helping teachers to predict and understand the problems that students have. The new book has twenty-two chapters dealing with learners who speak Dutch-Flemish, Scandinavian languages (except Finnish), German, French, Italian, Spanish, Catalan, Portuguese, Greek, Russian, Polish, Farsi, Arabic, Turkish, South Asian languages (with a separate chapter on Dravidian languages), West African languages, Swahili, Malay/Indonesian, Japanese, Chinese, Korean and Thai. An audio cassette and audio CD are available separately. These contain authentic examples of the various accents described in the book." http://www.loc.gov/catdir/description/cam021/00046785.html.
Keywords: Englisch; English language -- Study and teaching -- Foreign speakers; Interference (Linguistics); Ausländer; Fremdsprache; Englischunterricht; Interferenz -- Linguistik; Muttersprache